Isolation, Media Optimization, and Industrial Application of Cellulase-Producing Bacteria from Coir Industry Waste soil - Eglin Juno B K; Dr. A L Hema Latha (The Bioscan, 2026)
Cellulases are crucial biocatalysts for the sustainable conversion of lignocellulosic biomass into fermentable sugars, enabling biofuel, paper, and textile industries to reduce their reliance on chemical processes. This study reports the isolation, optimization, and industrial application of cellulase-producing bacterial strains, Bacillus sp. (S3) and Bacillus pacificus (S4), isolated from coir industry waste soils in Kanyakumari District, Tamil Nadu, India. The isolates were identified through morphological, biochemical, and molecular analyses, including 16S rRNA sequencing. Optimization experiments investigated the influence of pH, temperature, incubation time, carbon and nitrogen sources, and metal ions on cellulase production.